Decrease in reproductive desires among non-parent heterosexual women during the COVID-19 pandemic in Poland: the role of epidemiological stress, socioeconomic status, and reproductive rights - Marcinkowska, Urszula M.; Kasparek, Krzysztof K.; Zabdyr-Jamróz, Michał; Kozłowska, Marta; Nenko, Ilona (Frontiers in Public Health, 2025)
IntroductionDeterioration of economic conditions, societal uncertainty, and negative expectations about the future have all been linked to delayed childbearing plans. All these negative circumstances can be related to epidemiological stress, which in turn becomes one of the culprits for changes in fertility plans. This study aims to analyze the individual factors that decrease the probability of wanting to have children after exposure to epidemiological stress from the coronavirus disease 2019 (COVID-19) pandemic.MethodsRecruitment was conducted between April and July 2021. Participants who were heterosexual, non-parent, and non-pregnant without a diagnosis of infertility completed an online, anonymous survey providing information on sociodemographic variables, COVID-19 exposure, COVID-19-related stress, and changes in their reproductive desires. Multiple logistic regression models were used to analyze the data. Participants were also given the opportunity to provide a descriptive explanation for changes in fertility desires due to the pandemic or the political situation (abortion restrictions coinciding with the pandemic in Poland), which was then used for qualitative analysis.ResultsA total of 706 participants completed the survey (mean age = 28.11, SD = 4.87, min = 19, max = 47). We found that (1) the desire to have children decreased in 43.3% of respondents, and (2) women with higher levels of epidemiological stress were more likely to report a decrease in their desired number of children than the less-stressed ones, after adjusting for potential covariates (aOR = 1.064, 95%CI = 1.03–1.10, p < 0.001). Disease exposure yielded no significant results (aOR = 0.862, 95% CI = 0.73–1.02, p = 0.072). Additionally, 70% of participants declared a decrease in their willingness to have children due to the political situation. All models were adjusted for age, education, place of residence, socioeconomic and relationship status.ConclusionThe situation in Poland during the COVID-19 restrictions provided a unique combination of political and epidemiological stressors, showing that women’s reproductive desires were related to pandemic stress (less so with the exposure to disease) and limitation of reproductive rights.